From Local Integration Toward Ghettoized Community With Transnational Connections: The Case of Vietnamese Pagodas in Poland. Issue 4 (November 2019) - Szymanska-Matusiewicz, Grazyna; Bossak-Herbst, Barbara
A case study of Vietnamese pagodas operating in Warsaw and its surroundings in the past 25 years shows the strength with which local social and spatial conditions affect adaptation strategies of migrant institutions. Taking into account, the ecological perspective and the discourse of Vietnamese community concerning the role of temples enabled us to answer the question about the role of pagodas in maintaining local and transnational intragroup bonds and interactions with the majority society. This article shows how a process of local social and cultural integration that was beginning to emerge was significantly slowed down by spatial separation of the Vietnamese community and by this community's transnational connections getting on intensity.